Effects of microwave heating on oil palm mesocarp - Chang, J.; Law, Ming; Chan, Yen; Leo, C. (The Italian Association of Chemical Engineering, 2015)
Sterilization is an essential pre-treatment step in crude oil extraction process as to retain the quality and minimize the enzymatic activity within the fruits. This pre-treatment process on fresh fruit bunches often involves a large amount of steam and pre-treatment processes. Hence, this produces a large amount of palm oil mill effluent (POME) and empty fruit bunch wastes. Moreover, additional drying processes are required to reduce the fruits' moisture content for quality and storage purposes. Microwave energy is perceived as an alternative bringing improvement to the current process by introducing rapid heating as well as to improve process efficiency. The rapid heating process can effectively reduce power, energy and time required, yet capable of achieving the desired temperature through interaction between microwave, polar water molecules and charged ions in fresh fruit bunches. Other than that, microwave pre-treatment is a good alternative as it not only reduces the moisture content of fresh fruit bunches but also eliminates the production of POME, which is inevitable in the current process. Therefore, microwave technology is regarded as a clean process in the fresh fruit bunches pre-treatment. This paper reports the effects of microwave on the flesh of the oil palm fruits - mesocarp. Moisture content, dimensions and structure of the mesocarp are evaluated. The experimental results show that under the microwave treatment, the drying time required to reduce the moisture content of the mesocarp to 10 %, at power levels of 50-200 W, ranged from 2-35 min with the reduction of dimensions ranged from 3.6-6.2 %. Although varying the power level of microwave showed some degree of shrinkage, no significant changes were observed on the surface of the mesocarp.The experimental results demonstrated that microwave drying could provide a quicker drying process that resulted in least destruction occurred on the surface of the mesocarp.